Impact of histological response after neoadjuvant therapy on podocalyxin as a prognostic marker in pancreatic cancer - Annika Eurola (Nature Portfolio, 2021)
Abstract Podocalyxin overexpression associates with poor survival in pancreatic cancer (PDAC). We investigated whether podocalyxin expression correlates with treatment response or survival in neoadjuvant-treated PDAC. Through immunohistochemistry, we evaluated podocalyxin expression in 88 neoadjuvant and 143 upfront surgery patients using two antibodies. We developed a six-tier grading scheme for neoadjuvant responses evaluating the remaining tumor cells in surgical specimens. Strong podocalyxin immunopositivity associated with poor survival in the patients responding poorly to the neoadjuvant treatment (HR 4.16, 95% CI 1.56–11.01, p = 0.004), although neoadjuvant patients exhibited generally low podocalyxin expression (p = 0.017). Strong podocalyxin expression associated with perineural invasion (p = 0.003) and lack of radiation (p = 0.036). Two patients exhibited a complete neoadjuvant response, while a strong neoadjuvant response (≤ 5% of residual tumor cells) significantly associated with lower stage, pT-class and grade, less spread to the regional lymph nodes, less perineural invasion, and podocalyxin negativity (p < 0.05, respectively). A strong response predicted better survival (HR 0.28, 95% CI 0.09–0.94, p = 0.039). In conclusion, strong podocalyxin expression associates with poor survival among poorly responding neoadjuvant patients. A good response associates with podocalyxin negativity. A strong response associates with better outcome.